Turbulence and the Employment Experience of Older Workers - Etienne Lalé (Institute for the Study of Labor (IZA), 2016)
This paper provides a unified account of the trends in unemployment and labor force participation pertaining to the employment experience of older male workers during the past half-century. We build an equilibrium life-cycle model with labor-market frictions and an operative labor supply margin, wherein economic turbulence à la Ljungqvist and Sargent (1998) interact with institutions in ways that deteriorate employment. The model explains simultaneously: (i) the fall in labor force participation in the United States, (ii) the similar but more pronounced decline in Europe alongside rising unemployment rates and (iii) differences across European countries in the role played respectively by unemployment and labor force participation. The model also shows that policies that fostered early retirement may have exacerbated the deterioration of European labor markets: raising early retirement incentives to reduce unemployment among older workers tends to increase unemployment at younger ages, especially in turbulent economic times and under stringent employment protection legislation.
Keywords: E24; J21; J64; 330; job search; job loss; turbulence; European unemployment; labor force participation